Deviation Effect of Coaxiality on the Rock Brazilian Split - Zenghui Zhao; Mingzhong Zhang; Qing Ma; Baosen Chen (Advances in Mathematical Physics)
Tension failure is one of the main forms of instability in geotechnical engineering. Aiming at the calculation error caused by the loading direction deviation of the Brazilian disc splitting method, a mechanical model of a disc under chord loading was constructed firstly. Based on the theory of complex variable function, the analytic solutions of stresses in a circular disc were deduced, and the calculation error of the tensile strength under chord loading was characterized by defining the error impact rate. And the stress distribution of a disc and the law of rock fracture under chord loading were detailed analyzed through numerical calculation. Through numerical calculation, the stress distribution of the disc and rock failure law under chordwise loading are discussed in detail. The results show that the stress concentration near the loading point is stronger under the chordwise loading comparing with the radial loading, which makes the disc more vulnerable to produce compression failure near the loading point. The disc exhibits a maximum tensile stress and a minimum compressive stress at the intersection of the loaded string and the horizontal diameter, so that tensile rupture damage is likely to occur here. With the increase of deviation angle, the tensile strength measured by the Brazilian splitting test decreases gradually, and the influence rate of error increases significantly. The proposed analytical solution under chord loading provides theoretical guiding significance for nonradial splitting failure of a disc.